Corporate social responsibility review - Lizarzaburu Bolaños, Edmundo R. (2015)
This research paper represents a literature review of corporate social responsibility (CSR), as it has evolved and their use and impact in several countries. As a consequence of competitive markets, several entities must endeavor to reveal a picture of themselves as highly socially responsible enterprises. The increment in academic and practitioner interest in “Corporate Social Responsibility (CSR) has led the development of a set of definitions regarding the concept and their application” (Jamali and Mirshak 2007). The term is not a new concept (Taneja, Taneja and Gupta, 2011) it was developed since 1950´s. Nowadays, several literature presents substantial evidence that CSR activities can play a significant role in enhancing a firm’s value (Mahfuja, 2013). In this scenario, the following paper examines the broad progress of the ideas behind the concept though its origins and evolution in a country focus approach, practices implementation and literature available from different authors over the time. Also, we outline a set of core elements that many scholars associate this term with and finally we develop a special focus towards the stakeholders approach among all theories available on this matter.